Reduced serologic sensitivity to influenza A virus illness among inactivated influenza vaccinees. Issue 30 (24th June 2016) - Thompson, Mark G.; Gaglani, Manjusha J.; Naleway, Allison L.; Dowell, Samuel H.; Spencer, Sarah; Ball, Sarah; Levine, Min; Fry, Alicia
Abstract: We compared ≥4-fold increases in antibody titers by hemagglutination inhibition assay to RT-PCR results among 42 adults with PCR-confirmed influenza A virus illnesses. Serologic sensitivity was higher among unvaccinated (69%, 95% confidence interval [CI] = 48–90%) than vaccinated healthcare personnel (38%, 95% CI = 29–46%) in a 2010–11 prospective cohort.